Ambitious Politicians : The Implications of Career Ambition in Representative Democracy - Öhberg, Patrik (Book collections on Project MUSE., 2017)
"Research shows that we mistrust people who seem too nakedly ambitious for power. Indeed, Madison warned of the dangers from ambitious politicians. And yet, in the United States, with relatively weak parties, personal ambition for power is almost essential as candidates must create their own campaigns. In Europe many think that personal ambition tends to be subordinated to the goals of the party because political parties are much stronger and more disciplined. This is a study of the role of political ambition in Europe, comparing it to the United States. The author finds that personal ambition plays a different role in Europe but one that is changing. In the age of Donald Trump it is timely to ask whether countries are better served by politicians who seek higher office because of personal ambition or by those who subordinate their personal goals to the needs of the party or the country"--